Dangerous liaisons: molecular basis for a syndemic relationship between Kaposi’s sarcoma and P. falciparum malaria - Conant, Katelyn L.; Kaleeba, Johnan A. (Frontiers in Microbiology, 2013)
The most severe manifestations of malaria (caused by P. falciparum) occur as a direct result of parasitemia following invasion of erythrocytes by post-liver blood-stage merozoites, and during subsequent cyto-adherence of infected erythrocytes to the vascular endothelium. However, the disproportionate epidemiologic clustering of severe malaria with aggressive forms of endemic diseases such as Kaposi’s sarcoma, a neoplasm that is etiologically linked to infection with Kaposi’s sarcoma-associated herpesvirus [KSHV]), underscores the significance of previously unexplored co-pathogenetic interactions that have the potential to modify the overall disease burden in co-infected individuals. Based on recent studies of the mechanisms that P. falciparum and KSHV have evolved to interact with their mutual human host, several new perspectives are emerging that highlight a surprising convergence of biological themes potentially underlying their associated co-morbidities. Against this background, ongoing studies are rapidly constructing a fascinating new paradigm in which the major host receptors that control parasite invasion (Basigin/CD147) and cyto-adherence (CD36) are, surprisingly, also important targets for exploitation by KSHV. In this article, we consider the major pathobiological implications of the co-option of Basigin/CD147 and CD36 signaling pathways by both P. falciparum and KSHV, not only as essential host factors for parasite persistence but also as important mediators of the pro-angiogenic phenotype within the virus-infected endothelial microenvironment. Consequently, the triangulation of interactions between P. falciparum, KSHV, and their mutual human host articulates a syndemic relationship that points to a conceptual framework for prevalence of aggressive forms of Kaposi’s sarcoma in malaria endemic areas, with implications for the possibility of dual-use therapies against these debilitating infections in resource-limited parts of the world